Threshold Learning Outcome 3: Inquiry and problem-solving - Low, S.; Bennett, Sarita (Office for Learning and Teaching, 2016)
The Threshold Learning Outcomes (TLO) 3 Inquiry learning and problem-solving closely references TLO 3 for science (Jones et al. 2011). TLO 3.1, identifying contemporary issues and opportunities in agriculture is unique to agriculture TLO3. The Good Practice Guide for TLO 3 for science (Kirkup & Johnson 2013) provides a comprehensive review of the literature supporting inquiry learning and problem-solving, its development, successful delivery and implementation within higher education. This chapter highlights the main similarities and identifies the key differences between TLO 3 for science and TLO 3 for agriculture by: 1. providing background information on the role of inquiry learning and problem solving in professional agricultural practice 2. a discussion of learning strategies and activities that could be used to develop TLO3 3. providing case studies that are working examples of the development and implementation of learning strategies and assessment across year levels of undergraduate programs in agriculture and agribusiness 4. highlighting the challenges and opportunities that exist for the implementation of inquiry learning and problem-solving in an undergraduate program.